Akad Self-Service-Laundry in The Perspective of Fiqh Muamalah - Jakfar, Moham; Kumala DS, Agustina (Et-Tijarie, 2023)
Self-service laundry service is an innovation in the laundry business that is different from conventional laundry services. On the other hand, Fiqih Muamalah emphasizes that every contract/transaction must meet the provisions and run in accordance with the principles of Islamic law to realize benefits and justice.The type of research used is field research, which is qualitative descriptive, namely research by collecting data in accordance with the actual data and then the data is compiled, processed, and analyzed to provide an overview of the existing problem Primary data was obtained through observation and interviews with self-service laundry owners in Madura. Meanwhile, secondary data comes from references to books, journals, research results, and other materials related to the problem being researched.The results of this research are that the practice that applies to self-service laundry is the practice of ijarah 'ala al-manfa'ah contract. The practice began with an agreement between the customer/consumer (musta'jir) and the laundry self-service party (mu'jir) regarding the rental of laundry facilities and equipment. Customers then exchange their banknotes for laundry coins that are used for washing and drying. As for the practice, the self-service laundry contract has fulfilled the provisions of the ijarah contract perfectly. However, in practice, it is necessary to clarify the provisions of rights and responsibilities if something happens that has not been agreed upon in the contract, such as if there is damage to laundry equipment when used by consumers.